Citrate-capped gold nanoparticles with a diameter of 14 nm alter the expression of genes associated with stress response, cytoprotection and lipid metabolism in CaCo-2 cells. (13th December 2021) - Wusu, Adedoja Dorcas; Sibuyi, Nicole Remaliah Samantha; Moabelo, Koena Leah; Goboza, Mediline; Madiehe, Abram; Meyer, Mervin
Abstract: Advancements in nanotechnology have provided insight into the unique opportunities for the application of nanomaterials such as gold nanoparticles (AuNPs) in medicine due to their remarkable properties, which includes low toxicity, large surface area, and the ease of synthesis and conjugation to other molecules. Therefore, AuNPs are often preferred for bio-applications. Citrate-capped AuNPs (cAuNPs) have been reported to be non-cytotoxic and are used in numerous studies as drug delivery vehicles to treat various diseases. However, the limitations of bioassays often used to assess the toxicity of AuNPs have been well documented. Herein, we investigate the cytotoxicity of 14 nm cAuNPs in the human colorectal adenocarcinoma (Caco-2) cell line. Treatment conditions (i.e. dose and exposure time) that were established to be non-toxic to Caco-2 cells were used to investigate the effect of cAuNPs on the expression of a Qiagen panel of 86 genes involved in cytotoxicity. Out of 86 studied, 23 genes were differentially expressed. Genes involved in oxidative stress and antioxidant response, endoplasmic reticulum (ER) stress and unfolded protein response, heat shock response, and lipid metabolism were more affected than others. While low concentrations of 14 nm cAuNPs was not cytotoxic and did not cause cell death, cells treated with these nanoparticles experienced ER and oxidative stress, resulting in the activation of cytoprotective cellular processes. Additionally, several genes involved in lipid metabolism were also affected. Therefore, 14 nm cAuNPs can safely be used as drug delivery vehicles at low doses.